(3JYdjb Ydi GddeYs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s ((3eMehO s)
(3ChdgG (B:s
(3gPG JYdjb eNJUQ LYdJg JhVjMkG Ydi GdebOeI GdeSeGg HGddeY ai Yde GdMSGH s
(3BNQgG (B:s
(3hef CQGO GdRjGOI aYdjg HGdhSjdI ddeUfa aEfgG ef CMSf GdeUfaGJ JeJ GddeY GdeSeGJ HGdMSGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs